Surface-treated steel sheet

By optimizing the multi-layer coating structure and chemical conversion treatment, the problem of yellowing of pre-coated metal sheets at high temperatures was solved, and the heat resistance to yellowing and appearance stability were improved.

CN120936491APending Publication Date: 2025-11-11NIPPON STEEL CORPORATION
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480021801.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-04
Filing Date
2024-04-03
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

Existing pre-coated metal sheets are prone to yellowing at high temperatures, affecting their appearance, and current technologies have not effectively solved the problem of vanadium compound oxidation and discoloration.

Method used

A multi-layer coating structure is adopted, with optimized parameters such as thickness, hardness, glass transition temperature, and vanadium compound particle size of the primer coating layer and the top coating layer. Combined with chemical conversion treatment of the coating layer, a composite structure of Zn coating, primer coating layer and top coating layer is formed.

Benefits of technology

It significantly improves the heat resistance to yellowing of the coating layer, maintains appearance stability, and prevents external discoloration through the concealment properties of vanadium compounds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120936491A_ABST
    Figure CN120936491A_ABST
Patent Text Reader

Abstract

[Problem] To further improve thermal yellowing resistance of a coating layer even when the coating layer contains a vanadium compound. [Solution] A surface-treated steel sheet according to the present invention has: a Zn-containing plating layer positioned on the surface of a steel sheet serving as a base material; a primer coating layer that is positioned on the Zn-containing plating layer and contains at least a vanadium compound; and an upper coating layer positioned on the primer coating layer, in which the average thickness of the primer coating layer is in the range of 3.0-15.0 [mu] m, the average thickness of the upper coating layer is in the range of 7.0-25.0 [mu] m, the Vickers hardness of the upper coating layer is in the range of 25-70 Hv, the Vickers hardness of the primer coating layer is 20 Hv or less, and the average thickness of the upper coating layer is in the range of 3.0-15.0 [mu] m. The difference between the Vickers hardness of the upper coating layer and the Vickers hardness of the primer coating layer is within the range of 5-50 Hv.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to surface-treated steel sheets. Background Technology

[0002] For steel sheet blanks intended for use in home appliances, building materials, automobiles, and other applications, pre-coated metal sheets with a pre-colored coating are being used to replace the previously used post-coated steel sheets that were painted after forming and processing. These pre-coated metal sheets are made by covering the surface of rust-proofed or galvanized steel sheets with a colored coating. These pre-coated metal sheets have an attractive appearance, excellent workability, and good corrosion resistance.

[0003] In the pre-coated metal sheet described above, in order to further improve the corrosion resistance of the pre-coated metal sheet, the following technology is proposed: the coating layer provided on the coating is a multi-layer structure such as a primer coating layer and an upper coating layer, and the primer coating layer contains vanadium compounds as anti-rust pigments (for example, see Patent Document 1 below).

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: International Publication No. 2017 / 035572 Summary of the Invention

[0007] The problem the invention aims to solve

[0008] The inventors conducted research on using the pre-coated metal sheet disclosed in Patent Document 1 as a blank for heat-exposed household appliances such as outdoor units of water heaters and air conditioners. They found that the coating layer applied to the plating sometimes develops a yellowish tint over time. When this hue change occurs (more specifically, heat-induced yellowing), the appearance of the household appliance changes. Therefore, it is clear that there is room for further improvement in the heat resistance to yellowing of the coating applied to the plating.

[0009] Therefore, the present invention was made in view of the above-mentioned problems, and the object of the present invention is to provide a surface-treated steel sheet that can further improve the heat resistance to yellowing of the coating layer even when it has a coating layer containing vanadium compounds.

[0010] Solution for solving the problem

[0011] To address the aforementioned issues, the inventors conducted in-depth research and concluded that the heat-induced yellowing described above is due to the oxidation and discoloration of vanadium compounds contained in the coating layer, resulting in a yellow hue. Based on this, the inventors derived the following concept: if even if the vanadium compounds undergo oxidation and discoloration, the oxidized vanadium compounds are not easily identifiable from the outside, then, as a result, the change in the appearance of the surface-treated steel sheet may be difficult to detect. Therefore, based on this concept, the inventors conducted in-depth research on a structure that makes the oxidized vanadium difficult to identify.

[0012] The main points of the present invention, obtained from the results of the above research, are as follows.

[0013] (1) A surface-treated steel sheet comprising: a Zn-containing coating on the surface of a steel sheet serving as a base material; a primer coating on the Zn-containing coating, comprising at least a vanadium compound; and an upper coating on the primer coating, wherein the average thickness of the primer coating is in the range of 3.0 to 15.0 μm, the average thickness of the upper coating is in the range of 7.0 to 25.0 μm, the Vickers hardness of the upper coating is in the range of 25 to 70 Hv, the Vickers hardness of the primer coating is 20 Hv or less, and the difference between the Vickers hardness of the upper coating and the Vickers hardness of the primer coating is in the range of 5 to 50 Hv.

[0014] (2) The surface-treated steel plate according to (1), wherein the glass transition temperature Tg of the film-forming component of the aforementioned primer coating layer is in the range of 0 to 40°C, and the glass transition temperature Tg of the film-forming component of the aforementioned upper coating layer is in the range of 40 to 70°C.

[0015] (3) The surface-treated steel sheet according to (1) or (2), wherein the average particle size of the aforementioned vanadium compound is in the range of 0.05 to 2.00 μm.

[0016] (4) The surface-treated steel sheet according to (1) or (2), wherein the content of the aforementioned vanadium compound in the aforementioned primer coating layer is in the range of 5% to 50% by mass relative to the total solid content of the aforementioned primer coating layer, the content of the film-forming component in the aforementioned primer coating layer is in the range of 30% to 80% by mass relative to the total solid content of the aforementioned primer coating layer, and the aforementioned vanadium compound and the aforementioned film-forming component are contained in such a manner that the total content of the aforementioned vanadium compound and the aforementioned film-forming component is less than 100% by mass of the total solid content of the aforementioned primer coating layer.

[0017] (5) The surface-treated steel sheet according to (3), wherein the content of the aforementioned vanadium compound in the aforementioned primer coating layer is in the range of 5% to 50% by mass relative to the total solid content of the aforementioned primer coating layer, the content of the film-forming component in the aforementioned primer coating layer is in the range of 30% to 80% by mass relative to the total solid content of the aforementioned primer coating layer, and the aforementioned vanadium compound and the aforementioned film-forming component are contained in such a manner that the total content of the aforementioned vanadium compound and the aforementioned film-forming component is less than 100% by mass of the total solid content of the aforementioned primer coating layer.

[0018] (6) The surface-treated steel sheet according to (1) or (2), wherein the aforementioned upper coating layer contains aluminum pigment.

[0019] (7) The surface-treated steel sheet according to (1) or (2), wherein a chemical conversion treatment coating layer is further provided between the aforementioned Zn-containing coating layer and the aforementioned primer coating layer.

[0020] The effects of the invention

[0021] As explained above, according to the present invention, even when the coating layer contains vanadium compounds, the heat resistance to yellowing of the coating layer can be further improved. Attached Figure Description

[0022] Figure 1A This is an explanatory diagram illustrating an example of the structure of a surface-treated steel sheet according to an embodiment of the present invention.

[0023] Figure 1B This is an explanatory diagram illustrating an example of the structure of the surface-treated steel sheet of this embodiment.

[0024] Figure 2A This is an explanatory diagram illustrating an example of the structure of the surface-treated steel sheet of this embodiment.

[0025] Figure 2B This is an explanatory diagram illustrating an example of the structure of the surface-treated steel sheet of this embodiment. Detailed Implementation

[0026] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the accompanying drawings. It should be noted that in this specification and the accompanying drawings, constituent elements having substantially the same functional configuration are labeled with the same reference numerals, thereby omitting repeated descriptions.

[0027] (Regarding surface-treated steel plates)

[0028] The following is a reference. Figures 1A to 2B The surface-treated steel sheet according to embodiments of the present invention will be described in detail below. Figures 1A to 2BThis is an explanatory diagram illustrating an example of the structure of the surface-treated steel sheet according to this embodiment.

[0029] <Regarding the overall structure of surface-treated steel plates>

[0030] like Figure 1A As schematically shown, the surface-treated steel plate 1 of this embodiment has a base steel plate 10, a Zn-containing coating 20 on one side surface of the base steel plate 10, a primer coating layer 30 on the Zn-containing coating layer 20, and an upper coating layer 40 on the primer coating layer 30. Additionally, as... Figure 1B As illustrated, the surface-treated steel plate 1 of this embodiment may also have a chemical conversion coating layer 50 between the Zn-containing plating layer 20 and the primer coating layer 30.

[0031] It should be noted that the Zn-containing coating 20, primer coating 30, upper coating 40, and chemical conversion treatment coating 50, which can be configured as needed, can also be as follows: Figure 2A and Figure 2B As shown schematically, it is disposed on both sides of the base steel plate 10.

[0032] The following is a detailed description of the various components of the surface-treated steel sheet 1 of this embodiment.

[0033] <Regarding the base material steel plate 10>

[0034] For example, various steel plates can be used as the base material steel plate 10, such as Al killed steel, ultra-low carbon steel containing Ti, Nb, etc., and high-strength steel containing strengthening elements such as P, Si, Mn, etc. in ultra-low carbon steel.

[0035] In addition, the thickness of the base steel plate 10 can be appropriately set according to the mechanical strength required by the surface-treated steel plate 1, for example, it can be set to about 0.2mm to 10.0mm.

[0036] <Regarding Zn-containing plating 20>

[0037] The Zn-containing coating 20 is located on the surface of the base steel plate 10 as described above. This Zn-containing coating 20 is formed by various zinc-based coatings. Examples of such zinc-based coatings include hot-dip galvanizing, electro-galvanizing, zinc-nickel alloy coating, alloyed hot-dip galvanizing, aluminum-zinc alloy coating, zinc-aluminum-magnesium alloy coating, zinc-vanadium composite coating, and zinc-zirconium composite coating.

[0038] In such zinc-based plating, especially as the Zn-containing plating layer 20, zinc-aluminum-magnesium alloy plating is preferred, and zinc-aluminum-magnesium-silicon alloy plating containing Al: 4 to 22% by mass, Mg: 1 to 10% by mass, Si: 0.0001 to 2.0000% by mass, with the balance being Zn and impurities, is more preferred.

[0039] [Al: 4-22% by mass]

[0040] By setting the Al content to 4% by mass or more, the corrosion resistance of the steel plate can be further improved. More preferably, the Al content is 5% by mass or more. On the other hand, by setting the Al content to 22% by mass or less, the saturation of the corrosion resistance improvement effect described above can be suppressed, and the corrosion resistance of the steel plate can be further improved. More preferably, the Al content is 16% by mass or less.

[0041] [Mg: 1-10% by mass]

[0042] By ensuring the Mg content is 1% by mass or more, the corrosion resistance of the steel sheet can be further improved. More preferably, the Mg content is 2% by mass or more. On the other hand, in the plating bath used to form the coating, by adjusting the Mg concentration in the manufactured Zn-containing coating 20 to 10% by mass or less, the scum in the plating bath can be stabilized, resulting in the stable production of the coated steel sheet. In the plating bath used to form the Zn-containing coating 20, more preferably, the Mg concentration in the manufactured Zn-containing coating 20 is 5% by mass or less.

[0043] [Si: 0.0001~2.0000% by mass]

[0044] By making the Si content 0.0001% by mass or more, the adhesion of the Zn-containing coating 20 (more specifically, the adhesion between the base steel plate 10 and the Zn-containing coating 20) can be further improved. On the other hand, by making the Si content 2.0000% by mass or less, the saturation of the adhesion improvement effect of the Zn-containing coating 20 can be suppressed, and the adhesion of the Zn-containing coating 20 can be further improved. The Si content is more preferably 1.6000% by mass or less.

[0045] Furthermore, in the Zn-containing coating 20 of this embodiment, a portion of the remaining Zn may be replaced by elements such as Fe, Sb, and Pb, either alone or in combination, comprising less than 1% by mass.

[0046] Examples of zinc-based coated steel sheets with a Zn-containing coating 20 having the chemical composition described above include hot-dip galvanized aluminum-magnesium alloy steel sheets with a Zn-6%Al-3%Mg alloy coating and coated steel sheets with a Zn-11%Al-3%Mg-0.2%Si alloy coating (e.g., "SuperDyma" manufactured by Nippon Steel Corporation).

[0047] Methods for measuring chemical composition

[0048] The chemical composition of the Zn-containing coating 20 can be measured using inductively coupled plasma atomic emission spectrometry (ICP-AES). A sample is collected from the steel sheet of interest undergoing surface treatment, with the primer and top coat layers removed beforehand. There are no particular limitations on the method for removing the primer and top coat layers; known methods can be used. For example, for the cut sample, the coating is peeled off under the following conditions to expose the steel sheet. First, a coating stripper (Neorever #160, manufactured by Sansai Chemical Co., Ltd.) is applied to the surface at room temperature and allowed to stand for approximately 5 minutes. Then, the coating is peeled off by rubbing with a hard sponge (e.g., Kanefel, manufactured by AION Co., Ltd.). The sample with the coating removed is then washed / dried. If the coating is not sufficiently removed at this point, the same steps can be repeated to remove the coating. Alternatively, the coating can be removed by using commercially available coating stripper or sandblasting. Next, the coating is dissolved in an acid-containing solution containing an inhibitor that suppresses corrosion of the base steel sheet, thereby obtaining an acid solution containing the coating components. There are no particular restrictions on the type of acid, as long as it can dissolve the coating; for example, an aqueous HCl solution can be used. The acid solution obtained by ICP-AES analysis can provide the overall average chemical composition of the coating. Furthermore, by measuring the area of ​​the coated surface and the mass of the sample before and after coating removal, the coating adhesion amount (g / m²) of the surface-treated steel sheet can also be obtained simultaneously. 2 It should be noted that, before dissolving with acid, a sealing tape can be applied to only one side of the sample to prevent the coating on that side from dissolving in the acid solution, thereby determining the amount of Zn-containing coating 20 adhering to each single side.

[0049] It should be noted that, as described above, the total amount of the Zn-containing coating 20 applied to both sides of the steel plate is preferably 30 g / m². 2 The above (i.e., 15g / m² per single side) 2 (Above). By making the adhesion amount 30g / m 2 The above ensures reliable corrosion resistance for zinc-coated steel sheets. More preferably, the total coating amount on both sides of the steel sheet is 40 g / m². 2 That's all. On the other hand, the total amount of coating on both sides of the steel sheet is preferably 600 g / m². 2 The following (i.e., 300g / m² per single side) 2 (The following). By making the adhesion amount 600g / m 2The following ensures the smoothness of the surface containing the Zn coating 20 and further improves corrosion resistance. More preferably, the coating adhesion amount is 550 g / m² on both sides of the steel plate. 2 the following.

[0050] <Regarding the primer coating layer 30>

[0051] A primer coating layer 30 is provided on the Zn-containing plating layer 20 as described above. In this embodiment, the primer coating layer 30 contains a vanadium compound as a rust-preventive pigment to improve corrosion resistance.

[0052] In this embodiment, if moisture containing acid or alkali is adhering to the surface of the surface-treated steel sheet 1, this moisture may penetrate the upper coating layer 40 and the primer coating layer 30 to reach the surface containing the Zn plating layer 20 and the chemical conversion treatment coating layer 50. At this time, because the primer coating layer 30 contains vanadium compounds, the vanadium compounds dissolve relative to the impregnated moisture containing acid or alkali, releasing vanadate ions. These vanadate ions react with the metal on the surface of the Zn plating layer 20 and the chemical conversion treatment coating layer 50 to generate various salts. The generated salts form a dense barrier layer near the interface of the Zn plating layer 20 and the chemical conversion treatment coating layer 50, thereby improving the corrosion resistance of the surface-treated steel sheet 1.

[0053] Examples of suitable vanadium compounds include calcium vanadate, magnesium vanadate, ammonium metavanadate, potassium vanadate, sodium vanadate, ammonium vanadate, phosphorus vanadate, and vanadium oxide. Among these compounds, vanadium compounds containing pentavalent vanadium are particularly preferred. Furthermore, calcium vanadate, magnesium vanadate, and ammonium metavanadate are preferred for their good balance of corrosion resistance and water resistance due to their moderate solubility. These vanadium compounds can be used individually or in combination. It should be noted that vanadium pentoxide is preferably not used due to its toxicity.

[0054] In the primer coating layer 30 of this embodiment, the vanadium compound is preferably contained in particulate form. More specifically, in the primer coating layer 30 of this embodiment, the vanadium compound is preferably in particulate form with an average particle size in the range of 0.05 to 2.00 μm.

[0055] By ensuring that the average particle size of the vanadium compound is 0.05 μm or more, thermal diffusion of the vanadium compound into the upper coating layer and improvement of corrosion resistance can be achieved during the coating and drying process. More preferably, the average particle size of the vanadium compound is 0.10 μm or more, and even more preferably, 0.50 μm or more.

[0056] On the other hand, by making the average particle size of the vanadium compound 2.00 μm or less, the vanadium compound can suppress the horizontal deviation of the coating and be easily fixed near the interface on the coating side. The average particle size of the vanadium compound is more preferably 1.50 μm or less, and even more preferably 1.00 μm or less.

[0057] It should be noted that the average particle size of the vanadium compounds contained in the primer coating layer 30 can be determined as follows.

[0058] First, the surface-treated steel plate 1, which will become the object, is cut to an appropriate size and embedded in resin so that the cross-section in the thickness direction can be seen. The cross-section is then ground. Next, the cross-section of the ground surface is observed using a scanning electron microscope (SEM) equipped with an electron probe microanalyzer (EPMA). More specifically, EPMA mapping analysis (accelerating voltage: 15kV) is performed on the primer coating layer 30 of the cross-section (ground surface) at a magnification of 6000x. At this time, V is selected as the target element, and mapping images are taken to determine the presence location and concentration of V.

[0059] Next, SEM images of the same location on the same sample were captured at 6000x magnification and compared with the previous EPMA mapping images to determine all vanadium compounds in the SEM images. On the SEM images, a 20μm measurement range was defined along the plane of the steel plate. The particle size (the longest diameter, or major axis, if not perfectly circular) of all vanadium compounds present in the primer coating layer 30 within this range was measured. Then, using the measured particle size values, the average value of the vanadium compounds was calculated, and this average value was taken as the average particle size of the vanadium compounds. In cases where multiple vanadium compounds aggregate, the aggregated compounds were considered as one, and their particle size (major axis) was measured.

[0060] In addition, the primer coating layer 30 of this embodiment preferably contains, in addition to the vanadium compound mentioned above, a film-forming component for maintaining the primer coating layer 30 as a coating.

[0061] More specifically, the primer coating layer 30 of this embodiment preferably contains an adhesive resin as a film-forming component.

[0062] The binder resin contained in the primer coating layer 30 can be, for example, a high-molecular-weight polyester resin, polyester resin, acrylic resin, epoxy resin, polyurethane resin, fluororesin, etc. Alternatively, a substance formed by crosslinking film-forming resin components such as modified resins of these resins with a crosslinking agent component of a mixture of butylated melamine resin, methylated melamine resin, butylmethyl mixed melamine resin, urea resin, isocyanate resin, etc. Furthermore, electron beam curable resins and ultraviolet curable resins can also be used as binder resins.

[0063] Furthermore, the crosslinking agent used as the adhesive resin described above is preferably an isocyanate-based curing agent. For example, a substance formed by crosslinking a film-forming resin component made of polyester resin using an isocyanate-based curing agent is preferred. The crosslinking points of the coating formed by isocyanate curing become dense urethane bonds, and can react with hydroxyl groups (-OH) present on the coating surface, thereby further improving the adhesion to the Zn-containing coating 20 and further improving corrosion resistance.

[0064] It should be noted that the following method is used to confirm that the adhesive resin is isocyanate-cured. First, the surface-treated steel plate to be used is cut to an appropriate size and resin is embedded in it, and the cross-section is ground. Then, the primer coating layer of the cross-section is measured by methods such as micro Fourier transform infrared spectroscopy (FT-IR) to confirm that the 1550 cm⁻¹ isocyanate-cured. -1 The absorption peak of the nearby carbamate bond, 2260 cm⁻¹ -1 The C=N absorption peak from isocyanate that appears nearby is sufficient.

[0065] Here, isocyanate resins used as curing agents include, for example, substances obtained by capping monomers, dimers, trimers, and prepolymers containing these isocyanates in their backbones with capping agents such as methanol, ethanol, butanol, propanol, phenol, cresol, chlorophenol, nitrophenol, hydrogenated phenol, acetylacetone, ethyl acetoacetate, ethyl malonate, lactams, phosgene, 1-chloro-2-propanol, and MEK oximes. However, the types of isocyanate resins and capping agents are not limited to those mentioned above. As isocyanate resins, lactam-terminated MDI and MEK oxime-terminated IPDI are particularly preferred.

[0066] In the primer coating layer 30 of this embodiment, the glass transition temperature (Tg) of the film-forming component composed of the above-described components is preferably 0°C or higher. By setting the glass transition temperature (Tg) of the film-forming component to 0°C or higher, it is possible to prevent a decrease in corrosion resistance due to insufficient cohesion of the primer coating layer 30, and to suppress the thermal diffusion of vanadium compounds to the upper coating layer 40 during coating and drying heating. Furthermore, it is preferable to achieve the hardness relationship between the primer coating layer 30 and the upper coating layer 40, as detailed below. The glass transition temperature (Tg) of the film-forming component is more preferably 5°C or higher, and even more preferably 10°C or higher.

[0067] On the other hand, the glass transition temperature (Tg) of the film-forming component is preferably 40°C or lower. By ensuring that the glass transition temperature (Tg) of the film-forming component of the primer coating layer 30 is below 40°C, it is possible to prevent a decrease in processability due to the primer coating layer 30 becoming too hard. Furthermore, it is easier to achieve the hardness relationship with the upper coating layer 40, as will be described in detail below, which is therefore preferable. The glass transition temperature (Tg) of the film-forming component is more preferably 35°C or lower, and even more preferably 30°C or lower.

[0068] It should be noted that the glass transition temperature Tg can be determined, for example, by cutting off the coating used as the test object and then using the resulting sample for differential scanning calorimetry (DSC).

[0069] In the primer coating layer 30 of this embodiment, it is preferable that the content of the vanadium compound is in the range of 5 to 50% by mass relative to the total solid content of the primer coating layer 30, the content of the film-forming component is in the range of 30 to 80% by mass relative to the total solid content of the primer coating layer 30, and the vanadium compound and the film-forming component are contained in such a way that the total content of the vanadium compound and the film-forming component is less than 100% by mass of the total solid content of the primer coating layer 30.

[0070] By ensuring that the vanadium compound content is 5% by mass or more relative to the total solids content of the primer coating layer 30, the surface-treated steel sheet 1 of this embodiment achieves superior corrosion resistance. More preferably, the vanadium compound content is 10% by mass or more, and even more preferably 15% by mass or more. On the other hand, by ensuring that the vanadium compound content is 50% by mass or less relative to the total solids content of the primer coating layer 30, the reduction in processability and heat-resistant yellowing can be suppressed, and superior corrosion resistance can be achieved. More preferably, the vanadium compound content is 40% by mass or less, and even more preferably 30% by mass or less.

[0071] Furthermore, by ensuring that the content of the film-forming component is 30% by mass or more relative to the total solid content of the primer coating layer 30, the desired heat resistance to yellowing and processability can be easily achieved as a whole as the primer coating layer 30. The content of the film-forming component is more preferably 40% by mass or more, and even more preferably 50% by mass or more. On the other hand, by ensuring that the content of the film-forming component is 80% by mass or less relative to the total solid content of the primer coating layer 30, and by including anti-rust pigments, the reduction in corrosion resistance is easily suppressed. The content of the film-forming component is more preferably 70% by mass or less, and even more preferably 65% ​​by mass or less.

[0072] Here, the content of vanadium compounds and film-forming components in the primer coating layer 30 is substantially the same as the content of vanadium compounds and film-forming components contained in the primer coating used to form the primer coating layer 30.

[0073] It should be noted that when determining the content of vanadium compounds and film-forming components as described above from the already manufactured surface-treated steel sheet, glow discharge emission spectroscopy (GDS) can be used, for example. The coating of interest is sputtered from the surface towards the coating layer, and the concentration distribution along the depth direction is measured for the main elements constituting the primer coating layer 30. Then, the average concentration of the measured main elements in the primer coating layer 30 is calculated. If the specific type of vanadium compound is known, the measured concentration is converted based on the known molecular weight of the vanadium compound to calculate the average concentration of vanadium compounds in the primer coating layer 30. If the specific type of vanadium compound is unknown, elemental analysis of the vanadium compound is performed on a cross-section of the primer coating layer 30 using a field emission electron probe microanalyzer (FE-EPMA). Once the type of vanadium compound is determined, its concentration can be measured using the method described above. The concentration of the film-forming component can be calculated by subtracting the mass percentage of vanadium compounds calculated using the above method from 100% by mass.

[0074] The primer coating layer 30 of this embodiment may also contain rust-preventive pigments other than the aforementioned vanadium compounds. Examples of such rust-preventive pigments include calcium ion-exchanged silica (commonly known as calcium silicate), aluminum tripolyphosphate, zinc phosphate, iron phosphate, aluminum phosphate, magnesium phosphate, magnesium oxide, calcium molybdate, aluminum molybdate, barium molybdate, water-dispersible silica, fumed silica, orthophosphoric acid, pyrophosphoric acid, metaphosphoric acid, diphosphoric acid, phosphorous acid, hypophosphoric acid, and their salts. When such rust-preventive pigments are included, the total content of rust-preventive pigments containing vanadium compounds is preferably 20% by mass or more and 60% by mass or less relative to the total solids content of the primer coating layer 30. More preferably, the total content of rust-preventive pigments containing vanadium compounds is 35% by mass or more and 50% by mass or less. Furthermore, the primer coating layer 30 of this embodiment may also contain, as needed, extender pigments such as precipitating barium sulfate, clay, and coloring pigments such as titanium dioxide. Furthermore, in addition to the rust-preventive pigments, extender pigments, and coloring pigments described above, the primer coating layer 30 of this embodiment may also contain additives such as colorants, viscosity modifiers, leveling agents, defoamers, and ultraviolet absorbers as needed.

[0075] The average thickness of the primer coating layer 30 in this embodiment ( Figures 1A to 2B The thickness (dp) of the primer coating layer 30 is in the range of 3.0 to 15.0 μm. Excellent corrosion resistance can be achieved by making the average thickness of the primer coating layer 30 3.0 μm or more. The average thickness of the primer coating layer 30 is preferably 4.0 μm or more. On the other hand, by making the average thickness of the primer coating layer 30 15.0 μm or less, the reduction in processability can be suppressed, and excellent corrosion resistance can be achieved. The average thickness of the primer coating layer 30 is preferably 10.0 μm or less.

[0076] It should be noted that the average thickness of the primer coating layer 30 can be determined by direct observation from the cross-section. Specifically, the surface-treated steel plate 1 is embedded in room-temperature drying epoxy resin in a manner that allows observation of its cross-section. After mechanical grinding of the embedded surface, the surface is observed using SEM. The thickness is measured at any multiple locations (e.g., 10 locations), and the average of the obtained thicknesses is taken as the average thickness of the primer coating layer 30.

[0077] <Regarding the upper coating layer 40>

[0078] The surface-treated steel sheet 1 of this embodiment has an upper coating layer 40 on the primer coating layer 30 as described above. The upper coating layer 40 contains film-forming components corresponding to the application and can be formed into one or more coatings.

[0079] In this embodiment, the upper coating layer 40 preferably contains an adhesive resin as a film-forming component. Examples of adhesive resins include high-molecular-weight polyester resins, polyester resins, acrylic resins, epoxy resins, polyurethane resins, and fluororesins. Alternatively, a substance formed by crosslinking film-forming resin components such as modified resins of these resins with a crosslinking agent component of butylated melamine resin, methylated melamine resin, butylmethyl mixed melamine resin, urea resin, isocyanate resin, or a mixture of these resins may be used. Furthermore, electron beam curable resins and ultraviolet curable resins may also be used as adhesive resins.

[0080] In the upper coating layer 40 of this embodiment, the glass transition temperature (Tg) of the film-forming component composed of the components described above is preferably 40°C or higher. By setting the glass transition temperature (Tg) of the film-forming component to 40°C or higher, it is possible to prevent a decrease in corrosion resistance due to insufficient cohesion of the upper coating layer 40, and during the application and drying heating of the upper coating layer 40, the thermal diffusion of vanadium compounds from the primer coating layer 30 to the upper coating layer 40 can be suppressed. Furthermore, it is preferable to achieve the hardness relationship with the primer coating layer 30 more easily, as detailed below. The glass transition temperature (Tg) of the film-forming component is more preferably 45°C or higher, and even more preferably 50°C or higher.

[0081] On the other hand, the glass transition temperature (Tg) of the film-forming component is preferably 70°C or lower. By ensuring that the glass transition temperature (Tg) of the film-forming component of the upper coating layer 40 is below 70°C, it is possible to prevent a decrease in processability due to the upper coating layer 40 becoming too hard. Furthermore, it is preferable to achieve the hardness relationship with the primer coating layer 30, as will be described in detail below. The glass transition temperature (Tg) of the film-forming component is more preferably 65°C or lower, and even more preferably 60°C or lower.

[0082] Here, the glass transition temperature Tg can be measured using differential scanning calorimetry (DSC) in the same manner as described above.

[0083] In this embodiment, the upper coating layer 40 may contain a coloring pigment as a film-forming component, which can achieve a yellowing hue that is not easily noticeable. Therefore, as a whole, the yellowing of the coating is not easily noticeable from the outside of the surface-treated steel plate 1.

[0084] Examples of such coloring pigments include various aluminum pigments. By further containing aluminum pigments in the upper coating layer 40, the upper coating layer 40 exhibits a metallic appearance, making yellowing of the coating difficult to detect from the outside.

[0085] In addition to aluminum pigments as described above, known inorganic and organic pigments can also be used as coloring pigments. Examples of inorganic pigments include titanium dioxide, zinc oxide, zirconium oxide, calcium carbonate, barium sulfate, kaolin, carbon black, and iron oxide. Examples of organic pigments include Hansa Yellow, pyrazolone orange, phthalocyanine, and azo pigments.

[0086] The average thickness of the upper coating layer 40 in this embodiment ( Figures 1A to 2B The thickness (du) of the upper coating layer 40 is in the range of 7.0 to 25.0 μm. Excellent corrosion resistance can be achieved by making the average thickness of the upper coating layer 40 7.0 μm or more. Preferably, the average thickness of the upper coating layer 40 is 10.0 μm or more. On the other hand, by making the average thickness of the upper coating layer 40 25.0 μm or less, the reduction in processability can be suppressed, and excellent corrosion resistance can be achieved. Preferably, the average thickness of the upper coating layer 40 is 20.0 μm or less.

[0087] Here, the average thickness of the upper coating layer 40 can be measured in the same way as the average thickness of the primer coating layer 30.

[0088] <Regarding the relationship between the Vickers hardness of the primer coating layer 30 and the top coating layer 40>

[0089] In the surface-treated steel plate 1 of this embodiment, the Vickers hardness of the primer coating layer 30 is lower than that of the upper coating layer 40, and the difference between the Vickers hardness of the upper coating layer 40 and the Vickers hardness of the primer coating layer 30 is in the range of 5 to 50 Hv.

[0090] By making the Vickers hardness of the primer coating layer 30 lower than that of the upper coating layer 40 (in other words, the Vickers hardness of the upper coating layer 40 is higher than that of the primer coating layer 30), vanadium can be prevented from physically penetrating into the upper coating layer 40. Therefore, when the surface-treated steel sheet 1 is exposed to heat, the thermal diffusion of vanadium compounds from the primer coating layer 30 to the upper coating layer 40 can be prevented. Furthermore, by making the Vickers hardness of the primer coating layer 30 lower than that of the upper coating layer 40, the stress applied to the surface-treated steel sheet 1 can be relaxed using the primer coating layer 30. This prevents the coating layer from peeling off from the surface-treated steel sheet, maintaining the processing adhesion of the surface-treated steel sheet.

[0091] Specifically, the Vickers hardness of the primer coating layer 30 is below 20 Hv, and the Vickers hardness of the upper coating layer 40 is in the range of 25 Hv to 70 Hv.

[0092] Here, the Vickers hardness of the primer coating layer 30 is preferably 15 Hv or less. It should be noted that there is no specific specification for the lower limit of the Vickers hardness of the primer coating layer 30, but it is practically around 5 Hv. Furthermore, the Vickers hardness of the primer coating layer 30 is preferably 10 Hv or more.

[0093] In addition, the Vickers hardness of the upper coating layer 40 is preferably in the range of 28Hv to 65Hv.

[0094] Furthermore, if the difference in Vickers hardness between the upper coating layer 40 and the primer coating layer 30 is less than 5 Hv, thermal diffusion of vanadium compounds as described above cannot be prevented. Therefore, the difference in Vickers hardness between the upper coating layer 40 and the primer coating layer 30 is 5 Hv or more. Thus, in the surface-treated steel sheet 1 of this embodiment, improved heat resistance to yellowing can be achieved. Preferably, the difference in Vickers hardness between the upper coating layer 40 and the primer coating layer 30 is 10 Hv or more.

[0095] On the other hand, if the difference in Vickers hardness between the upper coating layer 40 and the primer coating layer 30 exceeds 50 Hv, the upper coating layer 40 becomes too hard, resulting in the inability to achieve the desired processing adhesion. Therefore, the difference in Vickers hardness between the upper coating layer 40 and the primer coating layer 30 is 50 Hv or less. Preferably, the difference in Vickers hardness between the upper coating layer 40 and the primer coating layer 30 is 40 Hv or less.

[0096] It should be noted that the relationship between the Vickers hardness of the primer coating layer 30 and the upper coating layer 40 can be achieved by adjusting the types and mixing of the film-forming components that make up each coating layer, and controlling the degree of crosslinking density in each coating layer.

[0097] It should be noted that the Vickers hardness of the primer coating layer 30 is determined by measuring a specified position of the primer coating layer 30 in a cross-section along its thickness direction. More specifically, the surface-treated steel plate 1 of interest is embedded in room-temperature drying epoxy resin in a manner that allows observation of its cross-section, and its embedded surface is mechanically ground. In the obtained cross-section, the position of the interface between the primer coating layer 30 and the layer located on the side of the base steel plate 10 that is closer to the base steel plate 10 than the primer coating layer 30 is determined. Using a commercially available hardness tester capable of performing indentation tests according to ISO 14577 (e.g., FISCHER INSTRUMENTS KK FISCHERSCOPE HM2000, etc.), the Vickers indenter (square pyramidal diamond indenter) is inserted to a depth of 1 μm in 10 seconds at a position 1 μm from this interface toward the side of the upper coating layer 40, and the Vickers hardness is measured. Such measurements are performed at multiple locations (e.g., 10 locations) at a position 1 μm from the interface toward the upper coating layer 40, and the average value of the obtained measurements is taken as the Vickers hardness of the primer coating layer 30.

[0098] Furthermore, the Vickers hardness of the upper coating layer 40 is determined by inserting an indenter into the surface of the upper coating layer 40 according to the indentation test of ISO 14577. More specifically, using a commercially available hardness tester (e.g., FISCHERSCOPE HM2000 manufactured by FISCHERINSTRUMENTS KK), the indenter is inserted into the surface of the upper coating layer 40 to a depth of 5 μm for 10 seconds, and the Vickers hardness is measured. Such measurements are performed at multiple locations (e.g., 10 locations) on the surface of the upper coating layer 40, and the average of the obtained measurements is taken as the Vickers hardness of the upper coating layer 40.

[0099] <Regarding the chemical conversion treatment coating layer 50>

[0100] In this embodiment, the chemical conversion coating layer 50 is formed by various chemical conversion treatments between the Zn-containing plating layer 20 and the primer coating layer 30 as needed.

[0101] The chemical conversion treatment coating layer 50 of this embodiment contains, for example, one or more selected from the group consisting of silane coupling agents, resins, zirconium compounds, silica, phosphates and their salts, fluorides, vanadium compounds, and tannins or tannic acid. By including the chemical conversion treatment coating layer 50 of this embodiment with the components described above, the film-forming properties after coating with the chemical conversion treatment solution, the barrier properties (density) of the coating against corrosive agents such as moisture and / or corrosive ions, and the adhesion of the coating to the plated surface can be improved, thus contributing to improved corrosion resistance of the coating.

[0102] The following is a detailed description of the components that may be included in the chemically converted coating layer 50 as described above, with examples provided.

[0103] (Silane coupling agent)

[0104] Examples of silane coupling agents include 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropylmethyldimethoxysilane, 3-(2-aminoethyl)aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropylmethyldiethoxysilane, 3-(2-aminoethyl)aminopropylmethyldimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 3-methacryloyloxypropylmethyldimethoxysilane, 3-methacryloyloxypropyltriethoxysilane, 3-methacryloyl... 3-Methyltriethoxysilane, N-2-(N-vinylbenzylaminoethyl)-3-aminopropyltrimethoxysilane, N-2-(N-vinylbenzylaminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(N-vinylbenzylaminoethyl)-3-aminopropyltriethoxysilane, N-2-(N-vinylbenzylaminoethyl)-3-aminopropylmethyldiethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane Dimethyldimethoxysilane, methyltrimethoxysilane, dimethyldimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, vinyltriacetoxysilane, 3-chloropropyltrimethoxysilane, 3-chloropropylmethyldimethoxysilane, 3-chloropropyltriethoxysilane, 3-chloropropylmethyldiethoxysilane, 3-anilinepropyltrimethoxysilane, 3-anilinepropylmethyldimethoxysilane, 3-anilinepropyltriethoxysilane, 3-anilinepropylmethyldiethoxysilane, vinyltrimethoxysilane, vinylmethyldimethoxysilane Silanes, vinyltriethoxysilanes, vinylmethyldiethoxysilanes, octadecyldimethyl[3-(trimethoxysilyl)propyl]ammonium chloride, octadecyldimethyl[3-(methyldimethoxysilyl)propyl]ammonium chloride, octadecyldimethyl[3-(triethoxysilyl)propyl]ammonium chloride, octadecyldimethyl[3-(methyldiethoxysilyl)propyl]ammonium chloride, 3-chloropropylmethyldimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, methyltrichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, etc. The amount of silane coupling agent added to the chemical conversion treatment agent used to form the chemical conversion treatment coating layer 50 can be, for example, set to 2–80 g / L. When the amount of silane coupling agent added is less than 2 g / L, the adhesion to the coating surface is insufficient, and the processing adhesion of the coating layer may be reduced. Furthermore, when the amount of silane coupling agent added exceeds 80 g / L, the cohesion of the chemically converted coating layer 50 is insufficient, and the processing adhesion of the coating layer may be reduced. One type of silane coupling agent can be used, or two or more types can be used in combination.

[0105] [Zirconium compounds]

[0106] Examples of zirconium compounds include: zirconium propionate, zirconium butyrate, zirconium tetraacetylacetone, zirconium monoacetylacetone, zirconium diacetylacetone, zirconium monoacetylacetone, zirconium acetoacetate, zirconium acetylacetone combined with ethyl diacetylacetone, zirconium acetate, zirconium monostearate, zirconium carbonate, ammonium zirconium carbonate, potassium zirconium carbonate, and sodium zirconium carbonate. The amount of zirconium compound added to the chemical conversion agent used to form the chemical conversion treated coating layer 50 can be set to, for example, 2 to 80 g / L. When the amount of zirconium compound added is less than 2 g / L, the adhesion to the coating surface is insufficient, and the processing adhesion of the coating layer may be reduced. Furthermore, when the amount of zirconium compound added exceeds 80 g / L, the cohesion of the chemical conversion treated coating layer 50 is insufficient, and the processing adhesion of the coating layer may be reduced. This zirconium compound can be used alone or in combination with two or more.

[0107] [Resin]

[0108] The resin is not particularly limited; for example, known organic resins such as polyester resin, polyurethane resin, epoxy resin, phenolic resin, acrylic resin, and polyolefin resin can be used. To further improve adhesion to the coated steel sheet, it is preferable to use at least one resin (polyester resin, polyurethane resin, epoxy resin, acrylic resin, etc.) that has a forced site or polar functional groups in its molecular chain. The resin can be used alone or in combination of two or more types.

[0109] The resin content in the chemically converted coating layer 50 is preferably 0% by mass or more, more preferably 1% by mass or more, relative to the coating solids content. Furthermore, the resin content in the chemically converted coating layer 50 is preferably 85% by mass or less, more preferably 60% by mass or less, and even more preferably 40% by mass or less, relative to the coating solids content. When the resin content exceeds 85% by mass, the proportion of other coating components may decrease, thereby reducing the performance required for the coating other than corrosion resistance.

[0110] Silicon dioxide

[0111] As the silica, commercially available silica gels such as "Snowtex N," "Snowtex C," "Snowtex UP," and "Snowtex PS" manufactured by Nissan Chemical Co., Ltd., "Adelite AT-20Q" manufactured by ADEKA CORPORATION, or powdered silica such as Aerosil #300 manufactured by Nippon Aerosil Co., Ltd., or equivalent silica, can be used. The silica can be appropriately selected according to the properties of the steel sheet to be surface treated. The amount of silica added to the chemical conversion agent used to form the chemical conversion coating layer 50 is preferably, for example, 1 to 40 g / L. When the amount of silica added is less than 1 g / L, the processing adhesion of the coating layer may decrease, and when the amount of silica added exceeds 40 g / L, the processing adhesion and corrosion resistance effects are likely to saturate, which is uneconomical.

[0112] Phosphate and its salts

[0113] Examples of phosphoric acid and its salts include, for instance, phosphoric acid such as orthophosphoric acid, metaphosphoric acid, pyrophosphoric acid, triphosphoric acid, tetraphosphoric acid, and their salts; ammonium salts such as triammonium phosphate and diammonium hydrogen phosphate; phosphonic acids such as aminotris(methylenephosphonic acid), 1-hydroxyethoxy-1,1-diphosphonic acid, ethylenediaminetetra(methylenephosphonic acid), and diethylenetriaminepenta(methylenephosphonic acid), and organophosphoric acids such as phytic acid, and their salts. It should be noted that, for salts of phosphoric acid, in addition to ammonium salts, examples include metal salts containing Na, Mg, Al, K, Ca, Mn, Ni, Zn, and Fe. Phosphoric acid and its salts can be used alone or in combination of two or more.

[0114] It should be noted that the content of phosphoric acid and its salts is preferably 0% by mass or more, more preferably 1% by mass or more, relative to the solid composition of the coating. Furthermore, the content of phosphoric acid and its salts is preferably 20% by mass or less, more preferably 10% by mass or less, relative to the solid composition of the coating. When the content of phosphoric acid and its salts exceeds 20% by mass, the coating may become brittle, reducing the processability of the coating during the forming process of the surface-treated steel sheet.

[0115] [Fluorides]

[0116] Examples of fluorides include: ammonium fluorozirconate, ammonium fluorosilicate, ammonium fluorotitanate, sodium fluoride, potassium fluoride, calcium fluoride, lithium fluoride, fluorotitanic acid, and fluorozirconic acid. These fluorides can be used alone or in combination with two or more other compounds.

[0117] It should be noted that the fluoride content is preferably 0% by mass or more, more preferably 1% by mass or more, relative to the coating solids content. Furthermore, the fluoride content is preferably 20% by mass or less, more preferably 10% by mass or less, relative to the coating solids content. When the fluoride content exceeds 20% by mass, the coating may become brittle, reducing the processability of the coating during the forming process of the surface-treated steel sheet.

[0118] [vanadium compounds]

[0119] Examples of vanadium compounds include: vanadium compounds obtained by reducing pentavalent vanadium compounds such as vanadium pentoxide, metavanadate, ammonium metavanadate, sodium metavanadate, and vanadium oxychloride to valences of 2-4 using a reducing agent; and vanadium compounds with oxidation states of 4-2, such as vanadium trioxide, vanadium dioxide, vanadium oxysulfate, vanadium oxyoxalate, vanadium oxyacetylacetonate, vanadium acetylacetonate, vanadium trichloride, phosphomolybdic acid, vanadium sulfate, vanadium dichloride, and vanadium oxide. These vanadium compounds can be used alone or in combination of two or more.

[0120] It should be noted that the content of vanadium compounds is preferably 0% by mass or more, more preferably 1% by mass or more, relative to the solid composition of the coating. Furthermore, the content of vanadium compounds is preferably 20% by mass or less, more preferably 10% by mass or less, relative to the solid composition of the coating. When the content of vanadium compounds exceeds 20% by mass, the coating may become brittle, reducing the processability of the coating during the forming process of the surface-treated steel sheet.

[0121] [Tannins or tannic acid]

[0122] Tannins or tannic acid can be any type of hydrolyzable tannin or condensed tannin. Examples of tannins and tannic acid include: witch hazel tannin, gallnut tannin, gallnut tannin, Terminalia chebula tannin, sage tannin, oak tannin, catechin, etc. The amount of tannin or tannic acid added to the chemical conversion agent used to form the chemical conversion treated coating layer 50 can be 2–80 g / L. When the amount of tannin or tannic acid added is less than 2 g / L, the adhesion to the coating surface is insufficient, and the processing adhesion of the coating layer may be reduced. In addition, when the amount of tannin or tannic acid added exceeds 80 g / L, the cohesion of the chemical conversion treated coating layer 50 is insufficient, and the processing adhesion of the coating layer may be reduced.

[0123] In addition, in the chemical conversion treatment agent used to form the chemical conversion treatment coating layer 50, acids, bases, etc., may be added to adjust the pH within a range that does not impair performance.

[0124] After applying a chemical conversion treatment agent containing the various components described above to one or both sides of the zinc-plated steel sheet 10, it is dried to form a chemical conversion treatment coating layer 50. In the surface-treated steel sheet of this embodiment, it is preferable to form a coating layer with a concentration of 100 mg / m² per side on the Zn-containing coating 20. 2 The above-mentioned chemically converted coating layer 50. More preferably, the adhesion amount of the chemically converted coating layer 50 is 200 mg / m³. 2 The above is further preferred to be 500 mg / m³. 2 That's all. Furthermore, in the surface-treated steel sheet of this embodiment, it is preferable to form a Zn-containing coating 20 with a concentration of 1000 mg / m² per single side. 2 The following is a chemically converted coating layer 50. The preferred adhesion amount of the chemically converted coating layer 50 is 800 mg / m³. 2 The following is a further preferred value: 600 mg / m² 2 It should be noted that, although the film thickness of the chemically converted coating layer 50 corresponding to this adhesion amount also depends on the components contained in the chemically converted agent, it is approximately 0.1 to 1.0 μm. It should also be noted that the film thickness of this chemically converted coating layer 50 can be determined by direct observation of the cross-section.

[0125] The above is for reference only. Figures 1A to 2B The surface-treated steel plate 1 of this embodiment has been described in detail.

[0126] (Regarding the manufacturing method of surface-treated steel sheets)

[0127] Hereinafter, an example of the manufacturing method of the surface-treated steel sheet according to this embodiment will be briefly described.

[0128] First, the steel sheet used as the base material undergoes various pretreatments, such as alkali degreasing, water washing, and pickling, to produce a clean steel sheet surface. Then, a Zn-containing coating is formed on the surface of the base steel sheet. In this coating process, a plating bath with a composition capable of achieving the desired coating structure is prepared, and the Zn-containing coating is formed using various known methods.

[0129] For steel sheets with a Zn-containing coating, various known chemical conversion treatments for forming a chemical conversion coating are performed as needed. For example, a chemical conversion agent containing the desired components as described above is prepared, and the chemical conversion agent is applied to the surface of the Zn-containing coating. Here, the application of the chemical conversion agent as described above can be carried out by commonly known coating methods, such as roller coating, curtain coating, air spraying, airless spraying, dipping, bar coating, brush coating, etc.

[0130] For example, a primer coating layer is formed by applying a primer coating solution to the surface of the Zn-containing coating (or chemical conversion treated coating layer) as described above, and then heating and drying it. Here, the primer coating solution is prepared by containing a vanadium compound as described above (more preferably, a vanadium compound as described above and a film-forming component, and various additives as needed) in a solvent. The coating of the prepared solution can be performed using conventionally known coating methods, such as roller coating, curtain coating, air spraying, airless spraying, dipping, bar coating, brush coating, etc.

[0131] In this embodiment of the surface-treated steel sheet, to prevent the thermal diffusion of vanadium compounds when the surface-treated steel sheet is exposed to heat, it is preferable to suppress the convection of the coating liquid during heat drying to some extent. In order to suppress such convection of the coating liquid, in the manufacturing method of the surface-treated steel sheet of this embodiment, it is important to heat and dry the coating liquid by combining an induction heating (IH) device and a hot air drying device.

[0132] More specifically, by induction heating the coated steel sheet while blowing hot air onto the coating surface, the viscosity near the surface of the primer coating increases, and convection is suppressed. This reduces the amount of vanadium compounds immobilized on the surface side of the primer coating (the location at the interface with the upper coating layer during the application of the upper coating), improving heat resistance to yellowing.

[0133] A topcoat forming coating solution is applied to the surface of the primer film layer formed above, and then heated and dried to form the topcoat layer. Here, the topcoat forming coating solution is prepared by containing the film-forming components described above (and various additives as needed) in a solvent. The coating of the prepared coating solution can be performed using commonly known coating methods, such as roller coating, curtain coating, air spraying, airless spraying, dipping, bar coating, brush coating, etc., as described above.

[0134] Then, the coating liquid can be heated and dried by any method, such as hot air, near-infrared rays, far-infrared rays, induction heating, or a combination of these methods.

[0135] The above provides a brief description of the manufacturing method of the surface-treated steel plate according to this embodiment.

[0136] It should be noted that the present invention described above can also be applied to various metal plates other than steel plates, such as aluminum plates, zinc plates, stainless steel plates, and titanium plates. That is, the primer coating layer 30 and the upper coating layer 40 as described above can also be provided on the surface of various metal plates other than steel plates (and further, a chemical conversion treatment coating layer 50 can be provided as needed).

[0137] Example

[0138] Hereinafter, the surface-treated steel sheet of the present invention will be specifically described with reference to embodiments and comparative examples. It should be noted that the embodiments shown below are merely examples of the surface-treated steel sheet of the present invention, and the surface-treated steel sheet of the present invention is not limited to the examples described below.

[0139] (1) Steel plate

[0140] Four types of steel plates, A1 to A4, as shown below (all manufactured by Nippon Steel Corporation), were prepared. The steel plates used as the base material were 0.7 mm thick. Furthermore, these steel plates were subjected to a 60 mg / m³ treatment. 2 The chromate-free chemical conversion treated steel sheet (CT-E300 / Nihon Parkerizing Co., Ltd.) is described. The treatment solution used in the chemical conversion treatment contains a silane coupling agent as a component, and the coating layer formed by this chemical conversion treatment functions as the chemical conversion coating layer. It should be noted that the presence or absence of chemical conversion treatment is described in Tables 1-1 to 1-3 below.

[0141] A1: Hot-dip galvanized steel sheet

[0142] A2: Hot-dip galvanized Zn-6 (mass%), Al-3 (mass%), Mg-coated steel sheet

[0143] A3: Hot-dip galvanized Zn-11 (mass %), Al-3 (mass %), Mg-0.2 (mass %), Si steel plate

[0144] A4: Steel plate (uncoated)

[0145] (2) Preparation of coatings for primer coating

[0146] A coating for forming a primer film was prepared. Toyobo Co., Ltd.'s polyester resins, namely "Vylon 500 (Tg: 4℃)," "Vylon GK880 (Tg: 84℃)," and "Vylon 550 (Tg: -15℃)," were dissolved in an organic solvent (a solvent prepared by mixing cyclohexanone and Solvesso 150 (trade name) in a 1:1 mass ratio). Here, by adjusting the mixing ratio of these polyester resins, the glass transition temperature (Tg) of the primer film after heat drying was adjusted to the values ​​shown in Tables 1-1 to 1-3.

[0147] Next, isocyanate "CORONATE 2536" (manufactured by Nippon Polyurethane Industry Co., Ltd.) was added as a curing agent. The mixing ratio of polyester resin to curing agent was 90:10 based on the mass ratio of solid components.

[0148] In addition, five compounds, B1 to B5, are prepared as rust-preventive pigments. These coating compositions are mixed with the specified particle size / specified amount shown in Tables 1-1 to 1-3 to prepare primer coatings.

[0149] B1: Calcium Vanadate

[0150] B2: Magnesium vanadate

[0151] B3: Calcium ion-exchanged silicon dioxide

[0152] B4: Aluminum tripolyphosphate

[0153] B5: Magnesium oxide

[0154] (3) Preparation of coating for top coating

[0155] A coating for forming an upper coating layer was prepared. Similar to the primer coating described above, "Vylon 500 (Tg: 4℃)," "Vylon GK880 (Tg 84℃)," and "Vylon 550 (Tg -15℃)," all polyester resins manufactured by Toyobo Co., Ltd., were dissolved in an organic solvent (a solvent prepared by mixing cyclohexanone and Solvesso 150 (trade name) in a 1:1 mass ratio). Here, by adjusting the mixing ratio of these polyester resins, the glass transition temperature (Tg) of the heat-dried upper coating layer was adjusted to the values ​​shown in Tables 1-1 to 1-3.

[0156] Next, melamine resin "CYMEL 235" (manufactured by Mitsui Chemicals Co., Ltd.) was added as a curing agent. The mixing ratio of polyester resin to curing agent was 80:10 based on the mass ratio of solid components.

[0157] In addition, as coloring pigments, commercially available titanium dioxide is mixed into white coated pigments in the amounts specified in Tables 1-1 to 1-3, and commercially available aluminum flakes are mixed into metallic coated pigments.

[0158] (4) Sample preparation

[0159] The primer coating prepared as described above is applied to the surface of the galvanized steel sheet with an average dried film thickness as described in Tables 1-1 to 1-3, and then dried using the methods described in Tables 1-1 to 1-3. It should be noted that in Tables 1-1 to 1-3 below, the use of both a hot air drying apparatus and an induction heating (IH) apparatus is indicated as "using both". Then, the prepared top coat coating is applied with an average dried film thickness as described in Tables 1-1 to 1-3, and then dried using a hot air furnace.

[0160] For each surface-treated steel sheet obtained, the Vickers hardness of the primer coating and the top coating was measured according to the previously described method. It should be noted that in Tables 1-1 to 1-3 below, the value of "Vickers hardness of the top coating - Vickers hardness of the primer coating" is recorded as the difference in Vickers hardness between the layers.

[0161] [Table 1-1]

[0162]

[0163] [Table 1-2]

[0164]

[0165] [Table 1-3]

[0166]

[0167] After cutting multiple test plates from the samples obtained as described above, each test plate was evaluated from the perspectives of heat resistance to yellowing, corrosion resistance, and processability. The results are summarized in Tables 2-1 to 2-3 below.

[0168] <Heat resistance and yellowing>

[0169] The heat resistance to yellowing was evaluated based on the following criteria. The test plates were kept at 180°C for 20 hours, and the change in hue (ΔE) before and after the test was measured using a spectrophotometer (Suga Test Instruments Co., Ltd. colorimeter SC-T45). The evaluation was conducted according to the following criteria, with a score of 1 indicating failure.

[0170] Score 5: ΔE is less than 2

[0171] 4: ΔE is greater than 2 and less than 3

[0172] 3: ΔE is 3 or more but less than 5

[0173] 2: ΔE is greater than 5 and less than 6

[0174] 1: ΔE is 6 or higher

[0175] <Corrosion Resistance>

[0176] The corrosion resistance is evaluated based on the following criteria. After sealing the end faces of the test plate, an X-shaped cut is made on the coating on the steel plate surface using a cutting tool until a deep scratch is made into the steel substrate. A 360-hour salt spray test (SST) is conducted according to JIS Z 2371:2015. The maximum expansion width on one side from the X-cut section is measured and evaluated according to the following evaluation criteria. At this point, a score of 1 is considered unacceptable.

[0177] Rating 5: Less than 3mm

[0178] 4: 3mm or more and less than 4mm

[0179] 3: 4mm or more and less than 5mm

[0180] 2: 5mm or more and less than 6mm

[0181] 1: 6mm or more

[0182] <Processing tightness>

[0183] The processing adhesion was evaluated based on the following criteria. For the test plate, a 2T bending process was performed in a 20°C atmosphere. An adhesive tape (trade name: CELLOPHANE TAPE (registered trademark)) was then applied to the outside of the 2T bent portion and peeled off. The appearance of the peeled portion was observed, and the evaluation was conducted according to the following criteria. A score of 1 was considered unacceptable.

[0184] Rating 5: Almost no coating peeling was found (peeling area from the bending process section was less than 2%).

[0185] 4: In a very small number of cases, coating peeling was found (the peeling area from the bending process section was more than 2% but less than 5%).

[0186] 3: Coating peeling was found in a portion (the peeling area from the bending process section was more than 5% and less than 10%).

[0187] 2: Partial coating peeling was found (the peeling area from the bending process section is more than 10% and less than 20%).

[0188] 1. Overall coating peeling was observed (the peeling area from the bending process section was more than 20%).

[0189] [Table 2-1]

[0190] Table 2-1

[0191]

[0192] [Table 2-2]

[0193] Table 2-2

[0194]

[0195] [Table 2-3]

[0196] Table 2-3

[0197]

[0198] As can be seen from Tables 2-1 to 2-3 above, the surface-treated steel sheet corresponding to the embodiments of the present invention has excellent heat resistance to yellowing, corrosion resistance and processing adhesion. On the other hand, the surface-treated steel sheet corresponding to the comparative examples of the present invention does not have sufficient heat resistance to yellowing, corrosion resistance or processing adhesion.

[0199] The preferred embodiments of the present invention have been described in detail above with reference to the accompanying drawings, but the present invention is not limited to the examples described above. Those skilled in the art to which this invention pertains will readily conceive of various modifications or alterations within the scope of the technical concept described in the claims, and such modifications or alterations are, of course, also within the technical scope of this invention.

[0200] The embodiments disclosed herein are illustrative in all respects and not restrictive. The above embodiments can be omitted, substituted, or modified in various ways without departing from the appended claims, the technical scope and spirit of the invention as described below. For example, the technical features of the above embodiments can be arbitrarily combined without impairing their effects. Furthermore, based on such arbitrary combinations, the effects and functions of each technical feature involved in the combination can be obtained, and other effects and functions that are apparent to those skilled in the art according to the description herein can also be obtained.

[0201] Furthermore, the effects described in this specification are merely illustrative or exemplary, and not restrictive. That is, the technology of the present invention can achieve other effects, either in conjunction with or instead of the effects described above, that are obvious to those skilled in the art from the description herein.

[0202] It should be noted that the following configurations also fall within the technical scope of this invention.

[0203] (1) A surface-treated steel plate, comprising:

[0204] A Zn-containing coating is located on the surface of a steel plate that serves as the base material;

[0205] A primer coating layer, situated on the aforementioned Zn-containing plating layer, contains at least a vanadium compound; and

[0206] The upper coating layer is located on top of the aforementioned primer coating layer.

[0207] The average thickness of the aforementioned primer coating layer is in the range of 3.0–15.0 μm.

[0208] The average thickness of the aforementioned upper coating layer is in the range of 7.0–25.0 μm.

[0209] The Vickers hardness of the aforementioned upper coating layer is in the range of 25 to 70 Hv, the Vickers hardness of the aforementioned primer coating layer is below 20 Hv, and the Vickers hardness of the aforementioned primer coating layer is lower than that of the aforementioned upper coating layer. The difference between the Vickers hardness of the aforementioned upper coating layer and the Vickers hardness of the aforementioned primer coating layer is in the range of 5 to 50 Hv.

[0210] (2) The surface-treated steel plate according to (1), wherein the glass transition temperature Tg of the film-forming component of the aforementioned primer coating layer is in the range of 0 to 40°C.

[0211] The glass transition temperature (Tg) of the film-forming components of the aforementioned upper coating layer is in the range of 40–70°C.

[0212] (3) The surface-treated steel sheet according to (1) or (2), wherein the average particle size of the aforementioned vanadium compound is in the range of 0.05 to 2.00 μm.

[0213] (4) The surface-treated steel sheet according to any one of (1) to (3), wherein the content of the aforementioned vanadium compound in the aforementioned primer coating layer is in the range of 5% to 50% by mass relative to the total solid content of the aforementioned primer coating layer.

[0214] The content of the film-forming component in the aforementioned primer coating layer is in the range of 30% to 80% by mass relative to the total solid content of the aforementioned primer coating layer, and,

[0215] The aforementioned vanadium compound and the aforementioned film-forming component are contained in such a manner that the total content of the aforementioned vanadium compound and the aforementioned film-forming component is less than 100% by mass of the total solid content of the aforementioned primer coating layer.

[0216] (5) The surface-treated steel sheet according to any one of (1) to (4), wherein the aforementioned upper coating layer contains aluminum pigment.

[0217] (6) The surface-treated steel sheet according to any one of (1) to (5), wherein a chemical conversion treatment coating layer is further provided between the aforementioned Zn-containing coating layer and the aforementioned primer coating layer.

[0218] Explanation of reference numerals in the attached figures

[0219] 1. Surface-treated steel plate

[0220] 10. Base steel plate

[0221] 20 Zn-containing coating

[0222] 30 Primer coating layers

[0223] 40. Top Coating Layer

[0224] 50 Chemically converted coating layer

Claims

1. A surface-treated steel plate, comprising: A Zn-containing coating is located on the surface of a steel plate that serves as the base material; A primer coating layer, situated on the Zn-containing plating layer, containing at least a vanadium compound; and The upper coating layer is located on top of the primer coating layer. The average thickness of the primer coating layer is in the range of 3.0 to 15.0 μm. The average thickness of the upper coating layer is in the range of 7.0–25.0 μm. The Vickers hardness of the upper coating layer is in the range of 25 to 70 Hv, the Vickers hardness of the primer coating layer is below 20 Hv, and the difference between the Vickers hardness of the upper coating layer and the Vickers hardness of the primer coating layer is in the range of 5 to 50 Hv.

2. The surface-treated steel plate according to claim 1, wherein, The glass transition temperature (Tg) of the film-forming components of the primer coating layer is in the range of 0–40°C. The glass transition temperature (Tg) of the film-forming components of the upper coating layer is in the range of 40–70°C.

3. The surface-treated steel plate according to claim 1 or 2, wherein, The average particle size of the vanadium compound is in the range of 0.05 to 2.00 μm.

4. The surface-treated steel plate according to claim 1 or 2, wherein, The content of the vanadium compound in the primer coating layer is in the range of 5% to 50% by mass relative to the total solids content of the primer coating layer. The content of the film-forming component in the primer coating layer is in the range of 30% to 80% by mass relative to the total solid content of the primer coating layer, and, The vanadium compound and the film-forming component are contained in such a manner that the total content of the vanadium compound and the film-forming component is less than 100% by mass of the total solids content of the primer coating layer.

5. The surface-treated steel plate according to claim 3, wherein, The content of the vanadium compound in the primer coating layer is in the range of 5% to 50% by mass relative to the total solids content of the primer coating layer. The content of the film-forming component in the primer coating layer is in the range of 30% to 80% by mass relative to the total solid content of the primer coating layer, and, The vanadium compound and the film-forming component are contained in such a manner that the total content of the vanadium compound and the film-forming component is less than 100% by mass of the total solids content of the primer coating layer.

6. The surface-treated steel plate according to claim 1 or 2, wherein, The upper coating layer contains aluminum pigment.

7. The surface-treated steel plate according to claim 1 or 2, wherein, A chemically converted coating layer is also present between the Zn-containing plating layer and the primer coating layer.

Citation Information

Patent Citations

  • A hydraulically powered rotary actuator

    WO2017035572A1